New Insights Into the Archaeal Consortium of Tropical Sponges - Turon, Marta; Uriz, Maria J. (Frontiers in Marine Science, 2020)
Archaea is a poorly studied domain associated with sponges. Many questions that have been addressed for bacteria still remain largely unknown for archaea. In this study, we analysed the archaeal communities of 17 tropical sponge species from Nha Trang Bay (Vietnam) using archaea specific primers. We recorded patterns of diversity and spatial stability of these microbial communities and compared the results obtained with the bacterial communities, already reported in our previous study. In our study species, Shannon diversity was always lower for archaeal than for bacterial communities. The differences in alpha diversity as well as the presence of indicator phyla reported for the bacterial domain in High Microbial Abundance (HMA) and Low Microbial Abundance (LMA) could not be confirmed for the archaeal communities. Host identity was the main factor structuring the archaeal assemblages. Sponge archaea core was formed by few but very abundant ZOTUs, which contribute with a high proportion to the relative archaea abundance. The inclusion of the obtained sequences into phylogenetic trees allowed finding out whether or not they belonged to the so-called sponge clusters (SC). Our results showed that most of the Thaumarchaeota and Euryarchaeota sequences were more closely related to environmental samples than to sponge clusters, suggesting that they might be acquired from the seawater, which need to be verified. However, representatives of Woesarchaeota, which were major members of the archaea microbiome of two sponge species, formed a monophyletic tree, distantly related to any known environmental sequence.